2007
DOI: 10.1159/000106911
|View full text |Cite
|
Sign up to set email alerts
|

HCC in Living Donor Liver Transplantation: Can We Expand the Milan Criteria?

Abstract: Background: The tumor biology of hepatocellular carcinoma (HCC) affects recurrence after liver transplantation (LT), but most selection guidelines are based only on tumor size and number. The aim of the study is to evaluate the possibility of expanding the selection criteria in living donor LT (LDLT) without compromising patient survival by adding α-fetoprotein (AFP) in selection guideline. Methods: One hundred thirty-nine patients who received LDLT with the diagnosis of HCC and survived more than 3 months wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…In an effort to assess the impact of AFP changes, patients were grouped according to AFP at listing and at transplantation, and to whether they were within or beyond the cut-off level of 400 ng/ml. This cut-off was chosen from previous studies [4,18,20,24]. Four groups were created and intent-to-treat survival was first assessed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to assess the impact of AFP changes, patients were grouped according to AFP at listing and at transplantation, and to whether they were within or beyond the cut-off level of 400 ng/ml. This cut-off was chosen from previous studies [4,18,20,24]. Four groups were created and intent-to-treat survival was first assessed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Velocity variables were negative (showing an improvement) or positive (showing a worsening). For some analyses, previously published cut-offs of 400 ng/ml for AFP and 115 cm 3 for TTV were used [4,[17][18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…A growing number of cohort studies have shown that survival outcomes of transplant patients chosen under the UCSF criteria are comparable to that for Milan-qualified patients [34,35,36]. Other groups have proposed their own versions of expanded criteria [37,38,39,40,41], but the survival outcomes reported for patients chosen under these have yet to be validated in larger cohorts.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Ito et al reported that in patients with HCC focus number ≤10, tumour size ≤5 cm, and desgamma-carboxy-prothrombin level ≤400 mAU (arbitrary units)/ml (Kyoto criteria), the 5-year patient survival after LDLT is 86.7%, while in patients with HCC exceeding these criteria 5-year patient survival was 34% only [35,65]. Many Asian centres use their selfdeveloped criteria [35,[66][67][68][69][70]. Western countries are also open to change.…”
Section: Extension Of Criteriamentioning
confidence: 99%